A Mott insulator continuously connected to iron pnictide superconductors - Yu Song (Nature Portfolio, 2016)
Whether an actual Mott insulator phase exists in iron pnictides remains elusive. Here, Songet al. demonstrate an antiferromagnetic insulator phase persisting above the Néel temperature in NaFe1−xCuxAs, indicative of a Mott insulator, highlighting the role of electron correlations in high-Tcsuperconductivity.